“When I See … I Will Remember”: Exploring the Memorability of Rainbows and Stars in Genesis through Mnemonatures - Austin, Emma M. (Biblical theology bulletin, 2025)
The authors of the Old Testament/Hebrew Bible (OT/HB) interweave the text with references to the natural world, creating cognitive links between nature and the text which aid memorability. Twenty-first century readers, chronologically and often spatially removed from this natural context, risk missing the mnemonic function of these references to nature, and the interpretative insights that may flow from them. To bridge this gap, I develop and implement an approach that I term “mnemonature,” which highlights the way that the natural world aids memorability. Then, to test its applicability, I apply mnemonature to two case studies in Genesis, which links a rainbow to God’s covenant with Noah (9:12–17) and the stars with God’s promise to Abram of abundant descendants (15:1–6). Mnemonature is a tool for exploring the biblical authors use and nuance references to the natural world, the memorable qualities of nature in realia, and the role that references to nature play in aiding the text’s memorability.